Carbon capture and sequestration: The roles of agriculture and soils - Stout, Bill; Lal, Rattan; Monger, Curtis (International Journal of Agricultural and Biological Engineering, 2016)
Renewable energy as a replacement for fossil fuels is highly desirable, but the reality is that fossil fuels (especially coal and petroleum) will be major sources of global energy for many decades to come. Therefore, carbon capture is vital to reduce release of carbon emissions and other GHG’s to the atmosphere thereby mitigating global warming. This presentation is a review of the role of agriculture and soils in carbon capture. Carbon sequestration in soils is the process of transferring CO2 from the atmosphere into soils through crop residues. Soil carbon sequestration increases with practices long recommended to increase yields, such as no-till, manure application, agroforestry and cover cropping. It is a Win-Win-Win strategy―advancing food security, improving the environment, and mitigating global warming. Carbon enrichment in greenhouse culture is in widespread use and has been adopted by many commercial producers. It results in remarkable increases in yields of flowers and vegetables. Research has shown the same increase in yields of trees and field crops with higher CO2 concentrations. The question is, how can CO2 be applied to field crops to increase yields? Restoration of desertified lands would improve soil quality, increase the pool of C in soils and forests, reduce CO2 emission to the atmosphere, and improve soil quality. Sequestration of additional carbon in soils would reduce CO2 emissions to the atmosphere thus mitigating global warming. Reforestation of forests is important, but real trees have ecological limits. Artificial trees could be used to absorb CO2 from the air any place on the planet, from any source―power plants, vehicles, and all industrial applications. Addition of CO2 in irrigation water could reduce the pH and help restore alkaline soils. Research is needed to further clarify the cost and benefit of many agriculture technologies for capturing and storing carbon. Keywords: carbon capture, sequestration, soils, agriculture, parasitic cost of carbon capture and sequestration DOI: 10.3965/j.ijabe.20160901.2280 Citation: Stout B, Lal R, Monger C. Carbon capture and sequestration: The roles of agriculture and soils. Int J Agric & Biol Eng, 2016; 9(1): 1－8.